Haematotoxicity of craniospinal radiochemotherapy for metastatic paediatric high-grade glioma - Valentini, Chiara; Perwein, T.; Bison, B.; Gielen, G. H.; Knerlich-Lukoschus, F.; Bock, H. C.; Seidel, C.; Kortmann, R. D.; Sturm, D.; Benesch, M.; Nussbaumer, G.; Krischer, J. M.; et al. (Clinical oncology, 2025)
Aims - Paediatric high-grade gliomas (pedHGGs) have a dismal prognosis, often characterised by early and diffuse disease progression. Novel treatment approaches are urgently needed to improve outcomes. The upcoming SIOPE-HGG (High Grade Glioma)-01 trial will investigate upfront craniospinal radiochemotherapy (CSI-RCT) for newly diagnosed, nonmetastatic diffuse midline glioma/diffuse intrinsic pontine glioma (DMG/DIPG). As CSI-RCT is frequently avoided due to concerns over haematotoxicity, real-world feasibility data are critically needed. - Materials and methods - We retrospectively assessed haematological toxicity in 19 patients (aged 3-21 years) with metastatic pedHGG treated with CSI-RCT within the hirn tumor glioblastoma trial (HIT-HGG) and hospital in trial-glioblastoma (HIT-GBM) trial programmes (2002-2024). All patients received craniospinal irradiation (median dose: 35.2 Gy) using photon- or proton-based techniques, with concurrent chemotherapy: temozolomide (TMZ; n = 14) or PEI (cisplatin, etoposide, ifosfamide; n = 5). Haematological toxicities were graded according to Common Terminology Criteria for Adverse Events (CTCAE) v4.0. - Results - Grade 3 to 4 haematotoxicity was observed in 7 of 19 patients (36.8%). Chemotherapy was discontinued in two cases—one due to TMZ-induced aplastic anaemia (TIAA) and another due to thrombocytopaenia. The remaining patients tolerated full-dose CSI-RCT with manageable side effects, and no unplanned radiotherapy interruptions occurred. The haematotoxicity rate was comparable to or lower than previous reports, indicating that CSI-RCT is feasible with appropriate monitoring and management. - Conclusion - This is the largest cohort to date assessing haematological toxicity of upfront CSI-RCT in metastatic pedHGG. Despite notable haematotoxicity, treatment was largely feasible and well-tolerated. These findings support the integration of CSI-RCT into future clinical trials for newly diagnosed DMG/DIPG and provide a foundation for the upcoming SIOPE HGG-01 trial. Proton therapy may further reduce toxicity and warrants prospective evaluation.